Usability of aortic knob width as novel clinical predictor for coronary artery disease severity before elective coronary angiography - Cagan Efe, Suleyman; Oz, Ahmet; Yalcin, Gunisil; Karabag, Turgut (Annals of Medical Research, 2021)
Aim: In this study, we aimed to investigate the relationship between AKW and the severity of CAD in patients with stable CAD. Stable coronary artery disease (CAD) patients coronary artery disease severity is determined invasive coronary angiography scoring systems as SYNTAX and Gensini scores. Therefore, there is a need for noninvasive and easy to apply methods for determining the severity of the disease in stable CAD. Aortic knob width (AKW) is a measurable radiographic structure from chest X-ray.Material and Methods: The study included 168 patients with stable CAD ranging from 18 to 70 years old after exclusions criteria applied 114 patients examined. Patients grouped according to coronary artery vessel diameter narrowing above and below 70%. Patients Baseline characteristics, physical examination, medical treatments and laboratory findings recorded. The severity of CAD was evaluated by SYNTAX and Gensini scores. AKW measurement was also evaluated. Results: The two groups were statistically similar with respect to demographic properties and laboratory findings. Prior medications were similar between the groups. Furthermore percentage of diabetes mellitus and CRP levels were significantly different between groups (48.4%, 22% p:0.004 , 6.3±12, 2.4±4 p:0.049 respectively). AKW was significantly higher in group 1 compared to group 2 (41.1±6.2, 37.3±5.2; p=0.007). AKWs were correlated with Gensini and SYNTAX scores (r=0.25;p=0.007 and r=0.26;p=0.006 respectively). In a ROC analysis, the area under the curve value of AKW for CAD was 0.648 (95% CI: 0.544-0.752, p 22 were; DM (Odds ratio [OR]: 6,088, 95% CI: 1.617-22.927; P= 0.008) , AKW (OR: 1.122, 95% CI: 1.024-1.229;P= 0.013).Conclusion: To demonstrate the severity and complexity of coronary artery disease in stable coronary artery disease, noninvasive and simply calculated AKW can be used instead of invasively calculated the calculated SYNTAX and Gensini scores.
Keywords: Aortic knob width; coronary artery disease severity; SYNTAX Score